MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MELALUI BERMAIN TABUNG PINTAR DI KELOMPOK B2 TK BINTANG LAUT BAGANSIAPIAPI KABUPATEN ROKAN HILIR - Natalia Ngatini; Daviq Chairilsyah; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The development of beginning reading skills of children are still low. This is caused by teachers who lack of variation method, so that the child is less interested in learn to read. The purpose of this research is to improve the reading skills of children through play smart tube in Bintang Laut kindergarten Bagansiapiapi Rokan Hilir. This research is a classroom action research and the subject is a child in Bintang Laut kindergarten B2 group Bagansiapaiapi with the amount of twenty five people. The average yield in the first cycle increases the child's ability to read better than before, at the beginning of the second cycle of children reading ability increased very well. It can be inferred that the smart tube game can improve children's reading skills of the B2 group Kindergarten Bintang Laut Bagansiapiapi Rokan Hilir.Keywords: Early reading, smart tube